Compared Experiences from Teaching Full-Semester Research Software Engineering Courses at Four German Universities - Bertrand, Nikolas; Devkate, Akshay; Juckeland, Guido; Linxweiler, Jan; Peters, Sören; Remus, Steffen; Schöning-Stierand, Katrin; Lamprecht, Anna-Lena (Electronic Communications of the EASST, 2025)
Research Software Engineering has emerged as a critical discipline at the intersection of software development and research with the aim of enhancing the quality, reliability, and reproducibility of scientific software. In this paper we present a comparative analysis of the experiences gained from teaching full-semester Research Software Engineering (RSE) courses at four different universities in Ger- many. Despite its growing importance, there is limited literature on the pedagogical approaches and challenges encountered in teaching RSE courses, particularly at the university level. This paper investigates and contrasts the contexts, designs, and experiences of RSE courses offered at the TU Braunschweig, TU Dresden, University of Hamburg and University of Potsdam. By synthesizing the experiences and insights gleaned from these four universities, this study aims to provide valu- able guidance and best practices for educators seeking to develop or enhance RSE education initiatives.